The influence of multi-walled carbon nanotubes on single-phase heat transfer and pressure drop characteristics in the transitional flow regime of smooth tubes - Meyer, Josua P. (University of Pretoria, 2013)
Dissertation (MEng)--University of Pretoria, 2012.